Predisposing factors and health-care utilization in liver transplant recipients with takotsubo cardiomyopathy: A national analysis - Patel, Kishan; Bhatti, Salman; Black, Sylvester; Porter, Kyle; Hanje, James; Mumtaz, Khalid (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Aims and Objectives: Takotsubo cardiomyopathy (TCMP) is an acquired cardiomyopathy associated with physical, emotional, and surgical stress. Current literature on TCMP in liver transplant recipients (LTRs) is limited to case reports and case series. Methods: The Nationwide Readmission Database was utilized to identify all adults with an index admission for LT between 2010 and 2014 who developed TCMP. The prevalence of TCMP at the LT admission or readmission within the calendar year was examined. Predictors of development and health-care utilization of patients with and without TCMP in LTR were compared. Multivariable regression analysis was performed. Results: The prevalence of TCMP in LTRs was found to be 0.5% (141/28,067). Most of these patients developed early TCMP on the index admission for LT (n = 115; 82%). Older (57.5 ± 1.3 vs. 55.1 ± 0.3 years, P < 0.001) females (adjusted odds ratio [aOR]: 2.27; confidence interval [CI]: 1.20–4.27; P = 0.01) with ≥4 Elixhauser comorbidity (aOR: 2.36; CI: 1.15–4.83; P = 0.02) were predisposed to develop TCMP in LTRs. LT at a medium-sized center (aOR: 0.17; CI: 0.03–0.88) has a protective effect on the development of TCMP. Increased health-care utilization in the form of mechanical ventilation, hemodialysis, vasopressors, and intra-aortic balloon pumps is observed in patients with TCMP. This resulted in increased length of stay and cost in patients with TCMP. Moreover, increased mortality was seen in patients who developed TCMP within the same calendar year. Conclusion: This is the first report showing the prevalence of TCMP in LTRs to be 0.5%. Older females with increased comorbidity are predisposed to TCMP. Patients who developed TCMP necessitate a higher acuity of medical care and cause an increased health-care burden and ultimately experience an increase in mortality.
Keywords: Database; female; liver transplantation; outcomes; Takotsubo cardiomyopathy